1992
DOI: 10.1115/1.2899765
|View full text |Cite
|
Sign up to set email alerts
|

Tool Temperatures in Interrupted Metal Cutting

Abstract: This paper summarizes the results of theoretical and experimental studies of tool temperatures in interrupted cutting. In the theoretical study, the temperature in a semi-infinite rectangular corner heated by a time-varying heat flux with various spatial distributions is used to investigate the general nature of the tool temperature distribution. The results of this analysis are compared with infrared and tool-chip thermocouple cutting temperature measurements from interrupted end turning tests on 2024 aluminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(34 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Therefore, the direct calculation of the entire temperature distribution only works under idealized conditions and assumptions. In addition, many models only resolve the temperature distribution in defined areas of the cutting zone like tool, workpiece or chip [13][14][15] and often require a heat source as input variable. "In summary, there is no general agreement on a partition criterion for the heat transfer into the tool, the chip, and the workpiece, in conventional machining.…”
Section: State Of the Art mentioning
confidence: 99%
“…Therefore, the direct calculation of the entire temperature distribution only works under idealized conditions and assumptions. In addition, many models only resolve the temperature distribution in defined areas of the cutting zone like tool, workpiece or chip [13][14][15] and often require a heat source as input variable. "In summary, there is no general agreement on a partition criterion for the heat transfer into the tool, the chip, and the workpiece, in conventional machining.…”
Section: State Of the Art mentioning
confidence: 99%
“…10). According to Stephenson et al [16], an end mill is modeled as a semi-infinite rectangular corner, x ≥ 0, y ≥ 0, z ≥ 0, heated by a heat flux as shown in Fig. 11.…”
Section: Temperature Distribution and Thermal Stressmentioning
confidence: 99%
“…Stephenson et al [16] found that 15% of the heat generated transferred into the cutting tool whereas the heat fraction value stated by Komanduri et al [4] was 10 %. Blok`s energy partition analysis [17] is often employed as the analytical model for thermal analyses of metal cutting operations.…”
Section: Introductionmentioning
confidence: 96%